Comparative efficacy of remotely delivered mindfulness-based eating awareness training versus behavioral-weight loss counseling during COVID-19 - Ugarte Pérez, Carla; Cruzat-Mandich, Claudia; Quiñones Bergeret, Álvaro; Díaz-Tendero, Dafne; Gallegos, Marcela; Gil, Aurora A.; Cepeda-Benito, Antonio (Frontiers in Psychology, 2023)
Introduction Dysregulated eating (emotional eating, cue-elicited eating, and dietary restraint and restriction) has been linked to being overweight or obese. The present investigation used a random controlled trial (RCT) to test the differential efficacy of remotely delivered Mindfulness-Based Eating Awareness Training (MB-EAT) and Behavioral Weight Loss (BWL) counseling. Methods The sample was recruited through advertisements that offered help to people “with problems controlling their eating” or “interested in improving their relationship with food” (n = 135). Results Retention was low in both groups (42%), but not dissimilar to retention rates reported in related clinical trials delivered “in person.” Among the participants who completed treatment, we found no between-group differences in any of the treatment outcomes, but participants in both groups experienced significant increases in eating-related mindfulness [Mindful Eating Questionnaire (MEQ) and awareness [Multidimensional Assessment of Interoceptive Awareness (MAIA), and significant decreases in unhealthy eating patterns [Dutch Eating Behavior Questionnaire (DEBQ); Binge Eating Scale (BES), and weight over the course of treatment. Participants in both groups also experienced increases in self-reported depression and anxiety symptoms [Hospital Anxiety and Depression Scale (HADS)], although these increases likely reflected normative changes observed in the population at large during COVID-19. Discussion Overall, the results suggest that dysregulated eating and weight loss intervention delivered remotely via teleconference can be effective.